THE USE OF XML TECHNOLOGIES FOR EXCHANGING INFORMATION WITHIN A MULTI-AGENT SYSTEM - Buraga, Sabin; Alboaie, Sinica; Alboaie, Lenuta (International Journal of Computing, 2014)
This paper presents different XML-based techniques for exchanging information between the constituents of a multi-agent system. We expose a multi-agent infrastructure – called Omega – that can be considered as a hierarchical space of distributed objects set those models the Web resources. We suggest an XML/RDF-based model that can be used as a common approach for serialization and metadata description of the objects processed by the agents. Diverse relationships that can be established between the entities of a multi-agent system will also be expressed by different RDF constructs.